The scope and nature of retail marketing - Burt, Steve (Henry Stewart Talks, 2009)
Understanding retailing, Retailing and marketing, Retailers and the exchange process, Understanding customer values, Creating customer values, Communicating customer values, Delivering customer values, Holistic view of marketing, The retail bottom line
Reviewed at 2016/04/28